Developing textbook of basic science concepts based on ethnoscience Dalihan Natolu - Apriani Sijabat; F. Festiyed; A. Asrizal; Abdul Razak; Palma Juanta (Research and Development in Education (RaDEn), 2024)
This research aimed to develop a textbook on basic science concepts based on ethnoscience that is valid, practical, and effective. The research method was R&D and implemented five stages of the ADDIE model. The instrument used in this research is a local wisdom-based textbook validation sheet consisting of a material media, and language validation sheet. There are three experts as a validators according to their field of science, an ethnoscience-based textbook practicality sheet. This sheet serves to determine the practicality of valid textbook design and the effectiveness sheet for ethnoscience-based textbooks based on Natolu ethnoscience. The research results show that the average value of the validity test results for textbooks on basic science concept based on ethnoscience is 81.26% (valid). The effectiveness results show a score of 3.5, which means the textbook developed is included are effective. Based on those results, it can be conclude that the ethnoscience-based basic concept of science textbook is valid, effective, and practical so it is suitable for use in the learning process in the Basic Science course.